A Facile Asymmetric Approach to the Multicyclic Core Structure of Mangicol A. Issue 49 (10th October 2014) - Ying, Jun; Pu, Lin
Abstract Chiral propargylic ether‐based triene–ynes are synthesized with high enantiomeric purity by employing an asymmetric enyne addition to aldehydes catalyzed by 1, 1′‐bi‐2‐naphthol in combination with ZnEt2, Ti(OiPr)4 and dicyclohexylamine at room temperature. These substrates are found to undergo a one‐pot domino Pauson–Khand and Diels–Alder cycloaddition catalyzed by [RhCl(CO)2]2 under CO to generate a series of multicyclic products with high chemoselectivity and stereoselectivity. These products contain the multicyclic core structure of mangicol A which could facilitate the synthesis and study of this class of natural products.